Monoclonal antibodies to native noncollagenous bone-specific proteins. - Stenner, D D (1984)
Hybridoma technology was used for preparation of murine monoclonal antibodies of high titer against bone-Gla protein and osteonectin. A procedure of immunization and hybridization similar to that already described [Katzmann, J.A., Nesheim, M.E., Hibbard, L.S. & Mann, K.G. (1981) Proc. Natl. Acad. Sci. USA 78, 162-166; and Foster, W.B., Katzmann, J.A., Miller, R.S., Nesheim, M.E. & Mann, K.G. (1982) Thromb. Res. 28, 649-661] was used. However, in contrast to earlier studies, mice were immunized with an unfractionated protein mixture that had been extracted from bone under nondenaturing conditions. The extract was labeled with 125I by the chloramine-T method. After fusion and initial hybrid growth, screening was accomplished by a solid-phase radioimmunoassay with total 125I-labeled bovine bone protein extract as the tracer. The identities of antibody-bound 125I-labeled proteins were assessed by dissolution of the solid-phase immune complex in NaDodSO4 and subsequent electrophoresis and autoradiography. Clones producing specific antibody to a single protein were selected by limiting dilution. The identity of the proteins against which the specific antibodies were produced was confirmed by immunoprecipitation, electrophoresis, and autoradiography. From two fusions, 30 positive hybrids to bone-Gla protein were identified; 7 of these were subcloned and 1 has been expanded as an ascites tumor. One hybrid population was positive for osteonectin, a Mr 15,000 peptide, and for bone-Gla protein. By limiting dilution, the osteonectin clone was selected and subsequently expanded as an ascites tumor. Titration curves made using the respective 125I-labeled purified proteins show the ascites tumors to be producing antibody of high titer (I50 = 10(-6) for anti-bone-Gla protein and (I50 = 10(-5) for antiosteonectin. Both of the antibovine antibodies are cross-reactive with the corresponding human protein. Immobilized specific anti-bone-Gla protein has been used to isolate human bone-Gla protein from an EDTA extract of human cortical bone. Thus, this method offers the possibility of developing a complete library of monoclonal antibodies against these and other bone-specific proteins.